PENGEMBANGAN KEMAMPUAN SUMBER DAYA MANUSIA MELALUI PELATIHAN MICROSOFT OFFICE EXCEL PADA DINAS LINGKUNGAN HIDUP DAN KEHUTANAN PROVINSI BENGKULU - Ardi Ardi wijaya; Yulia Darnita; Yovi Apridiansyah; M. Sapta Firdaus; M. Dhaffa Giffari; M. Gilang Ramadhan (Gayaku Publisher, 2022)
In facing the era of globalization which is growing rapidly at this time, especially the development of increasingly advanced science and technology, it is very necessary to have an adequate skill to support the performance of employees at the Dinas Lingkungan Hidup dan Kehutanan Provinsi Bengkulu. This is because in service activities or in the form of making reports to superiors, employees and staff, especially in the administration section, they still have not utilized their full potential which is computerized in operating Microsoft Office programs. This condition certainly has an impact on the less than optimal performance of employees and staff in compiling and making reports quickly and efficiently. The purpose of this Community Service is to provide training and improve and maximize the potential of human resources on how to operate computers in the Microsoft Office Excel program for employees at the Dinas Lingkungan Hidup dan Kehutanan Provinsi Bengkulu, so that they can be better at making and compiling reports. The method of implementing Community Service activities is a method of training, practice and question and answer. While the target audience is employees and staff who want to maximize the existing potential by operating computers better and they are still not very well versed in making computerized reports. By holding Community Service Activities through training in operating computers, especially employees at the Dinas Lingkungan Hidup dan Kehutanan Provinsi Bengkulu, they can add insight and knowledge and improve employee performance more optimally in compiling and making reports faster and more efficiently. Key words: Science and Technology, Microsoft Office Excel, Training